Ethiopia - Traditional Medicine and the Bridge to Better Health - World Bank (Washington, DC, 2012)
The majority of Ethiopians depend on medical plants as their only source of health care, especially in rural areas where access to villages is lacking due to the absence of vehicular roads. The increasing scarcity of medicinal plant species represents a trend that should be immediately addressed. The health and drug policies of the Ethiopian Ministry of Health recognize the important role medical plants and traditional health systems play in health care. Unfortunately little has been done in recent decades to enhance and develop the beneficial aspects of traditional medicine including related research and its gradual integration into modern medicine. With the World Bank assistance, the Ethiopian government will soon start to implement the first conservation and sustainable use of medical plants project in Sub-Saharan Africa. The overall objective of the project is to initiate support for conservation, management, and sustainable use of medicinal plants for human and livestock health care.